Draft Outline of the Fifth Five-Year Plan (1974-79) Maharashtra State - Planning Commission (Planning Commission, 1974)
Removal of poverty and attainment of economic self-reliance are the two major tasks Basic which the country has set out to accomplish the other related objectives of the Plan include object, reduction of disparities in income and wealth, balanced regional development and establishment of a free and just society within the framework of a democratic political order.
Government of Maharashtra, Planning Department